Realism in Action
VII, 292 p.
Keywords: Realism in Action is a selection of essays written by leading representatives in the fields of action theory and philosophy of mind, philosophy of the social sciences and especially the nature of social action, and of epistemology and philosophy of science. Practical reason, reasons and causes in action theory, intending and trying, and folk-psychological explanation are some of the topics discussed by these leading participants. A particular emphasis is laid on trust, commitments and social institutions, on the possibility of grounding social notions in individual social attitudes, on the nature of social groups, institutions and collective intentionality, and on common belief and common knowledge. Applications to the social sciences include, e.g., a look at the Erklären-Verstehen controversy in economics, and at constructivist and realist views on archeological reconstructions of the past.